The Air Quality Index (AQI) At Universiti Tun Hussein Onn Malaysia (UTHM) Campus Pagoh - KHAIROL ANUAR, NURUL ALIA SYUHADA; ABDUL WAHID, ABDUL ZAKI; ABDUL RAHMAN, MOHAMMAD ASHRAF (Progress in Engineering Application and Technology, 2023)
An air pollutant is any substance that affects the natural nature of the atmosphere whether chemical, physical, or biological. Major pollutant of public health concern includes particulate matter, carbon monoxide, ozone, nitrogen dioxide, and sulfur dioxide. Indoor and outdoor air pollution are significant contributors to morbidity and death and are known to induce respiratory and other illnesses. The air quality index has already defined the parameter and the range of air quality. Based on the air quality, people can acquire extensive information on the many types of gases dissolved in the air. The air quality index can be classified into several categories. There are four levels of severity, which are good, moderate, poor, and severe. Since the Higher Education Hub in Bandar Universiti Pagoh was built, Pagoh town has expanded quickly and it is now one of the most commercialized towns in Muar. In Pagoh town near to UTHM Campus area, probability that the air quality index will be high when there are many cars and an extensive infrastructure of industries, offices, homes, and other buildings has been built all around the town to prepare the area for urbanization and industrialization. Monitoring the major pollutants of particulate matter (PM) 2.5 and 10, carbon dioxide (CO2) and carbon monoxide (CO) which can analyse and interpreted by determine the air quality index that polluted by several gases at UTHM Campus Pagoh area. To monitoring the air quality index, Universiti Tun Hussein Onn Malaysia (UTHM) has provided two tool that can monitoring the gases. E-sampler is a tool that can measure the air pollution index in airborne particulate matter (PM) which contain particulate matter gases 2.5 and 10. While the indoor air quality tool can detect carbon dioxide (CO2) and carbon monoxide (CO). From this tool, this will conduct whether the air quality index is good, moderate, unhealthy, unhealthy for sensitive group, vary unhealthy or hazardous.